2005
DOI: 10.2337/diacare.28.2.454
|View full text |Cite
|
Sign up to set email alerts
|

Are Granulocyte Colony–Stimulating Factors Beneficial in Treating Diabetic Foot Infections?

Abstract: OBJECTIVE -To assess the value of granulocyte colony-stimulating factor (G-CSF) as adjunctive therapy for diabetic foot infections.RESEARCH DESIGN AND METHODS -We systematically searched the medical literature (including Medline, Embase, LookSmart, and the Cochrane Library) for prospective randomized studies that used G-CSF as an adjunct to standard treatment for diabetic foot infections. Using a conventional meta-analysis, we pooled the relative risks (RRs) for outcomes of interest, including resolution of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
10

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 47 publications
0
38
0
10
Order By: Relevance
“…Similarly, granulocyte macrophage colony stimulating factor (GM-CSF) has been also showed promising for wound treatment in vitro, mainly due to the stimulation of VEGF production [58]. Other studies have given encouraging results in clinical trials on patients with venous stasis ulcers [59] and diabetic-foot ulcers [60]. However, cytokines should not be considered individually, because in vivo they function in complex networks and cascades, frequently exhibiting antagonism (the effects of one cytokine may be inhibited by another cytokine).…”
Section: Growth Factors and Cytokinesmentioning
confidence: 93%
“…Similarly, granulocyte macrophage colony stimulating factor (GM-CSF) has been also showed promising for wound treatment in vitro, mainly due to the stimulation of VEGF production [58]. Other studies have given encouraging results in clinical trials on patients with venous stasis ulcers [59] and diabetic-foot ulcers [60]. However, cytokines should not be considered individually, because in vivo they function in complex networks and cascades, frequently exhibiting antagonism (the effects of one cytokine may be inhibited by another cytokine).…”
Section: Growth Factors and Cytokinesmentioning
confidence: 93%
“…Foot ischemia certainly appears to be associated with an increased severity of an infection (36). Diabetic patients often have a diminished inflammatory response to injury or infection (37)(38)(39)(40)(41)(42)(43); this deficit could be further impaired by ischemia. Diminished blood flow could result in a lack of erythema or induration, visual cues of infection.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In contrast, the effect of G-CSF was studied primarily to determine whether its use may help eradicate infection, and published trials were of either too small or too short a term to demonstrate an effect on healing when it was included as a secondary endpoint. Nevertheless, a small meta-analysis suggested that G-CSF may lead to a reduced incidence of major amputation in limbthreatening infection [85].…”
Section: Discussionmentioning
confidence: 99%